2007
DOI: 10.1111/j.1462-2920.2007.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding the candidate enzyme for anaerobic activation of n‐alkanes in the denitrifying bacterium, strain HxN1

Abstract: Strain HxN1, a member of the Betaproteobacteria, can grow anaerobically by denitrification with n-alkanes. n-Alkanes are apparently activated by subterminal carbon addition to fumarate yielding (1-methylalkyl)succinates, the postulated enzyme being (1-methylalkyl)succinate synthase (Mas). Genes encoding this enzyme (mas) were searched for via proteins that were specifically formed in n-hexane-grown cells (in comparison with caproate-grown cells), as revealed by two-dimensional gel electrophoresis. Partial amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 42 publications
3
97
0
2
Order By: Relevance
“…The ion selection threshold for MS/MS was 500 counts, and an activation Q-value (effective collision energy) of 0. 25 and an activation time of 30 ms were also applied for MS/MS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion selection threshold for MS/MS was 500 counts, and an activation Q-value (effective collision energy) of 0. 25 and an activation time of 30 ms were also applied for MS/MS.…”
Section: Methodsmentioning
confidence: 99%
“…The Bss enzyme is a well-investigated close homolog of Nms, catalyzing fumarate addition in the initial reaction of anaerobic toluene degradation (34,40). Based on findings from comparative sequence studies, glycine radical-catalyzed fumarate addition has been shown to be a widely distributed initial reaction mechanism for anaerobic hydrocarbon degradation involving toluene and 2-methylnaphthalene, n-alkanes (12,13,25,51), m-xylene (33), m-and p-cresols (9), and ethylbenzene (32).…”
mentioning
confidence: 99%
“…These genes may well be active in the degradation of hydrocarbons other than toluene, which can also involve fumarate addition (Callaghan et al, 2008;Grundmann et al, 2008;Musat et al, 2009). Alternatively, it could indicate that intrinsic toluene-degrading microbial populations at the site have changed between the two time points of sampling (August 2004 andDecember 2006), which is supported by the fact that in 2004 we did not detect any 'F2'-lineage bssA genes at the site, whereas direct bssA-targeted fingerprinting of DNA from our SIP inoculum, taken from the same well as in 2004, did.…”
Section: Other Microbes Involved In Toluene Degradationmentioning
confidence: 99%
“…1B) (11,12). Additionally, alkyl-SSs, which function on alkyl chains including n-hexane, have also been discovered (13,14), although there is less known about the substrate specificity and mechanism of these enzymes. Together these enzymes form a large family of X-succinate synthases (XSSs) responsible for functionalization of a wide variety of hydrocarbon substrates, and the range of substrates is still growing.…”
mentioning
confidence: 99%